When do firms highlight their effective tax rate? - Vanessa Flagmeier; Jens Müller; Caren Sureth (Arbeitskreis Quantitative Steuerlehre (arqus), 2020)
This study examines the visibility of the GAAP effective tax rate (ETR) in firms' financial statements as a distinct disclosure choice. Applying a game-theory disclosure model for voluntary disclosure strategies of firms to a tax setting, we argue that firms face a trade-off in their ETR disclosure decisions. On the one hand, firms have an incentive to enhance their ETR disclosure when the ratio offers shareholders "favourable conditions", for example in terms of higher expected after-tax cash-flows. On the other hand, the disclosure of a favourable low ETR could attract the attention of tax auditors and the public and ultimately result in disclosure costs. We empirically test disclosure behaviour by examining the relation between disclosure visibility and different ETR conditions that reflect different stakeholder-specific costs and benefits. While we find that unfavourable ETR conditions are not highlighted, we observe higher disclosure visibility for favourable ETRs (smooth, close to the industry average, decreasing). Additional analyses reveal that this high visibility is characteristic of firm-years with only moderately decreasing ETRs at usual ETR levels, while extreme ETRs are not highlighted. Interestingly and in contrast to our main results, a subsample of family firms do not seem to highlight favourable ETRs.
Keywords: 330; Effective tax rate; Cost-benefit trade-off; Disclosure decision; Reputational costs; Tax disclosure